New Techniques of Weighted Sum Method for Solving Multi-Objective Geometric Programming Problems (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Multi-objective geometric programming problem is a type of optimization problem that wildly used in engineering problems. Until now there are not many optimization techniques that can easily compute this type of optimization problem. In this paper, we proposed two new techniques with algorithms to optimize multi-objective geometric programming problems. We created the first technique by using the weighted sum method and Arithmetic mean, and by using the weighted sum method and geometric mean we produced the second technique. These two methods are used to convert multi-objective geometric optimization problems to single-objective geometric optimization problems Some examples are considered to illustrate the results. The results were compared with other common techniques used in solving multi-objective engineering optimization problems.